A ZE25A-O3 Sensor-Based Solution for Continuous Ozone Level Measurement in LINAC Environments - Khasanah, Nur; Hudha, Lalu Sahrul; Jamiluddin, Jamiluddin; Ernita, Nevi; Bunawas, Bunawas; M, I Wayan Ari; Subroto, Rinarto (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Abstract Ozone (O₃) generated during LINAC operation can accumulate indoors and pose respiratory risks, yet many facilities lack continuous monitoring. We designed and validated a low-cost, electrochemical sensor platform—ZE25A-O₃ integrated with an Arduino Mega, on-board logging, and a Nextion HMI—for real-time surveillance in a LINAC suite. The sensor was calibrated at 24 °C and 40% RH against 0.5–1.5 ppm standards, yielding slope = 1.045, intercept = −0.04067 ppm, R² = 0.99984, and RMSE = 9.39 ppb, supporting reliable low-ppb quantification. Time series were aggregated into 30-min bins with centered 1-h rolling means to extract diurnal structure while suppressing short-term fluctuations. Field measurements showed a 20–30 ppb background with intermittent spikes exceeding 100 ppb (peaks ~150 ppb). A reproducible daily pattern emerged: late-morning minima (~20–21 ppb) followed by evening enhancement (~26–28 ppb), consistent with ventilation and operational schedule. Average conditions were below the Indonesian workplace limit of 100 ppb, but episodic exceedances motivate real-time alerts and ventilation management. This work demonstrates a practical approach for continuous exposure assessment and data-informed environmental control in radiotherapy facilities.